Alat Kontrol Temperatur Menggunakan Panel Surya untuk Mengurangi Tingkat Kematian pada Pembenihan Ikan Lele di Kabupaten Kediri - Eko Yohanes Setyawan; Yusuf Ismail Nakhoda; Basuki Widodo; Choirul Soleh (Jurnal Pengabdian Pada Masyarakat, 2019)
TEMPERATURE CONTROL DEVICES USING SOLAR PANELS TO REDUCE MORTALITY RATES IN CATFISH HATCHERIES IN KEDIRI REGENCY. Pelemahan District, Kediri Regency is one of the centers of catfish breeding that is visited by many industry players in the field of catfish enlargement for consumption. This nursery has been done for a long time in this region because of the good geographical and topographic conditions for catfish hatchery, so many entrepreneurs’ enlargement catfish for the consumption of buying catfish seeds in Kediri Regency. From the results of a survey of the Malang National Institute of Technology’s dedicated team for Pelemahan Subdistrict, there were several problems with the catfish breeding business, namely poor environmental conditions so that the number of dead fish caused by temperature changes caused the fish to become stressed. Water quality is a factor that must be cleaned because it is contaminated with catfish food and catfish feces. So that water circulation needs to be done, so a tool is made that can reduce the temperature of the water in the pool between 28-30 °C. The workings of the tool first measure the temperature of the water in the pond when the high temperature of the water pump will automatically turn on, until the temperature drops and to maintain clean water in the pool the water pump automatically turns on every three hours. Because the place of catfish is maintained which is sometimes far from home and to facilitate the maintenance of catfish, this tool is made easy to move, and using solar energy that is easily available. From the results of observing using a temperature controller in the pool can reduce the death rate due to stress and lack of oxygen.